Sleepy wear by Luciana : a sustainable sleepwear brand - Murschenhofer, Luciana Martina Henriette (2023)
Consumers are becoming increasingly conscious of the need to live a healthier and greener lifestyle by using less harmful products. Additionally, living in a world where the importance of truthful, restful nights is becoming progressively significant, offers an opportunity to develop a sustainable sleepwear brand that provides eco-friendly sleepwear sets without compromising quality and aesthetics. The importance of marketing planning and brand development to launch a new product is addressed in the context of the consumers raising concerns with their consumption patterns’ effects on their lifestyle and well-being. This project follows a mixed methods approach, using primary data collection, including focus groups, interviews and a questionnaire. The data collected, in combination with the use of secondary data, supported the development of a marketing plan for the launch of a new sleepwear brand. By interviewing potential customers in a focus group (N=5), conducting semistructured interviews (N=5), and completing a survey (N=150), this project explores and presents the development of a sleepwear brand and its marketing plan. The findings revealed that most people value qualities such as comfort, simple design, and temperature regulation and prefer light colors over heavy patterns and colorful sleepwear sets. Moreover, consumers are willing to spend more money on sustainable sleepwear even though it is not their main focus. These findings were valuable for the creation of the brand Sleepy Wear by Luciana and the development of the marketing plan for the brand.